Статистичний аналіз ризиків довгострокового безробіття на ринку праці України - Жерліцин, Д. М.; Тищенко, М. М.; Zherlitsyn, D. M.; Tyshchenko, M. M. (Причорноморський науково-дослідний інститут економіки та інновацій, 2020)
Ринок праці та рівень безробіття є ключовими складовими під час визначення ефективності сучасних економічних систем у будь-якій державі світу. У статі проаналізовано проблеми структурних диспропорцій між попитом і пропозицією на сучасному ринку праці. Розглянута динаміки показників безробіття за різними професійними групами в Україні. Представлений методичний підхід до оцінки рівня чистого довгострокового безробіття в межах певних професійних груп. Доведена економічна сутність поняття ризику довгострокового безробіття. Проведена оцінка ризиків довгострокового безробіття у розрізі окремих професійних груп на ринку праці України. Визначено взаємозв’язки професійно-кваліфікаційної структури незайнятого населення та наявних вакансій. Запропоновано метод оцінки ризиків довгострокового безробіття на основні використання статистичних методів. Оцінено довірчий інтервал рівня довгострокового безробіття в Украйні за окремими професійними групами. Визначено професійні групи зі значними рівнем довгострокового безробіття та суттєвою невизначеністю. Сформульовано напрямки розвитку наукових досліджень та практичних розробок щодо підвищення ефективності інструментів регулювання на ринку праці України.

The labor market and the unemployment rate are key components of the effectiveness of modern economic systems in any country of the world. The latest labor market trend is characterized by the presence of discrepancies and structural disproportion between supply and demand of labor, which might have both a negative and positive impact on economic development. Therefore, the purpose of the paper is to determine the essence of the concept of long-term unemployment risk and scientific and methodological justification of the features of its assessment. This article is based on the theoretical principles and methods of statistics; the system approach methods of defining the level of the long-term unemployment risks. The article analyzes the problems of structural disproportion between supply and demand in the modern labour market. The dynamics of unemployment rates for various professional groups in Ukraine is considered. The paper shows an original methodological approach to assessing the level of net long-term unemployment within certain professional groups. The economic essence of the concept of long-term unemployment risk is substantiated. The assessment of the risks of long-term unemployment in the context of individual professional groups in the labor market of Ukraine is presented. The interconnections of the vocational qualification structure of the unemployed population and the available vacancies are determined. A method of assessing the risks of long-term unemployment for the main use of statistical methods is proposed. The confidence intervals of the long-term unemployment rate in Ukraine for the individual professional groups are estimated. The results of the analysis identify which professional groups have a high level of long-term unemployment and significant uncertainty rate in Ukraine. The highest level of long-term unemployment is determined within the professional groups of legislators, senior administrators, managers, where the confidence interval is about 90-92%. The lowest level of long-term unemployment is burdened within the group of occupations of skilled workers with a tool, where the probability of remaining unemployed for a year varies between 23% and 57%. The authors formulate the development directions of scientific research and practical application for the efficiency improvement of the regulation instruments of the Ukrainian labor market.
Statistical analysis of the long-term unemployment risks for the Ukrainian labor market
Keywords: довгострокове безробіття; ринок праці; структурна диспропорція; професійна група; рівень ризику; довірчий інтервал; longterm unemployment; labor market; structural disproportion; professional group; risk level; confidence interval